New financial instruments and institutions opportunities and policy challenges - Fuchita, Yasuyuki, 1958-; Litan, Robert E., 1950- (Brookings Institution Press, 2007)
"Presents research from experts in academia and the financial industry on financial instruments and new financial institutions, contrasting developments in the United States and Japan. Highlights innovative ways in which Japanese financiers and government officials have learned from the United States regarding the introduction of new instruments into their market"--Provided by publisher.